A Fragment of a Diagonal Star Table from the Los Angeles County Museum of Art (LACMA M80.202.500) - Dieleman, Jacco.
This article offers the edition of two columns of a so-called diagonal star table that are inscribed on a wooden batten (LACMA M80.202.500) that was once affixed to the underside of the lid of a Middle Kingdom coffin. The two columns follow the Kenmet table format, bringing the number of known artifacts preserving Kenmet tables up to eleven. The item is without provenance, but, like the other Kenmet tables, is likely from the site of Assiut and dates to the early Middle Kingdom.